Heterogeneity in the uptake, attendance and outcomes in a clinical trial of a total diet replacement weight loss programme - Astbury, N; Tudor, K; Aveyard, P; Jebb, S (BMC, 2020)
Background: Trials have shown total diet replacement programmes (TDR) are safe and effective for weight loss in primary care. However, it is not clear whether participant characteristics affect uptake, attendance or effectiveness of the programme.